The Concept of Studying the Value of Science in the Philosophy of Science - Nurwahidah, Alfi; Baiti, Fajar; Aisyah, Siti; Udin, Tamsik (Penerbit Hellow Pustaka, 2026)
This study aims to examine and analyze the values of science from the perspective of the philosophy of science, including epistemological, ethical and moral, pragmatic, aesthetic, socio-cultural, economic, and philosophical values. This study employs a library research method by reviewing relevant literature such as books, academic journals, and scholarly works related to the philosophy of science and axiology. The findings indicate that these values are interconnected and form an integrated framework in the development and application of scientific knowledge. Epistemological values ensure the validity of knowledge, ethical and moral values guide scientific responsibility, pragmatic values emphasize usefulness, aesthetic values enhance communication and clarity, socio-cultural values ensure social relevance, economic values contribute to welfare, and philosophical values provide meaning and direction for science. Therefore, integrating scientific values is essential for fostering a knowledgeable, ethical, and sustainable human civilization.